2021
DOI: 10.1080/02656736.2021.1936218
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided thermal ablation for papillary thyroid microcarcinoma: a multicenter retrospective study

Abstract: Purpose: Ultrasound-guided thermal ablation (including microwave ablation [MWA] and radiofrequency ablation [RFA]) has emerged as a remarkable technology for the treatment of benign and malignant diseases. The objective of this multicenter study was to assess the efficacy and safety of thermal ablation in a large cohort of patients with papillary thyroid microcarcinoma (PTMC). Materials and methods: Retrospective study of 725 patients who underwent MWA/RFA at 11 centers between March 2015 and March 2020. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The 2015 ATA guidelines suggest that patients with low risk PTMCs can also be actively monitored (15); however, some patients are unable to undergo long-term follow-up because of anxiety about the disease, and in these cases, ablation of PTMC is a compromise between surgery and observation. A multicenter PTMC ablation study conducted in China that included 11 centers and 725 patients (21) showed a significant reduction in tumor size at 6 months after ablation compared with that before ablation. On ultrasound, 515 (71.0%) PTMCs disappeared completely.…”
Section: Review Thermal Ablation Study Of Papillary Thyroid Microcarc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2015 ATA guidelines suggest that patients with low risk PTMCs can also be actively monitored (15); however, some patients are unable to undergo long-term follow-up because of anxiety about the disease, and in these cases, ablation of PTMC is a compromise between surgery and observation. A multicenter PTMC ablation study conducted in China that included 11 centers and 725 patients (21) showed a significant reduction in tumor size at 6 months after ablation compared with that before ablation. On ultrasound, 515 (71.0%) PTMCs disappeared completely.…”
Section: Review Thermal Ablation Study Of Papillary Thyroid Microcarc...mentioning
confidence: 99%
“…In addition, the rich blood supply to the thyroid gland can lead to transient bleeding at the end of the ablation, although this can be relieved with compression. Finally, a small number of patients experience complications such as altered thyroid function (24,27,49,50,60,77) and cough (21,36,45) after thermal ablation, which normally resolve during the postoperative period.…”
Section: Complicationsmentioning
confidence: 99%
“…25 Currently, treatment regimens for PTMC range from thyroidectomy, AS, and US-guided RFA. 5,8,15 Herein, the current study sought to evaluate the effects of US-guided RFA on PTMC and influencing factors, and the obtained findings revealed that US-guided RFA exhibits better efficacy, safety, and postoperative recovery and lower recurrence risk for PTMC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, AS treatment is not suitable for all PTMC cases and some physicians hesitate to adopt the management policy in daily clinical practice. 10 The last decade has also witnessed the surge and adoption of US-guided ablation techniques such as laser ablation, 11 microwave ablation, [12][13][14] or radiofrequency ablation (RFA) 15 for successfully treating patients with benign thyroid nodules, PTMC, or metastatic lymph nodes at risk of surgery. Additionally, USguided RFA treatment is highly safe and effective for PTMC, and it can serve as a minimally invasive therapy for patients with PTMC who refuse AS or surgical treatment.…”
mentioning
confidence: 99%
“…Microwave ablation (MWA) has been widely used in the treatment of benign thyroid nodules [ 5 ] and papillary thyroid cancer (PTC) [ 6 , 7 ]. Studies have demonstrated that MWA can preserve thyroid function in patients even with bilateral thyroid nodule ablation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%